The Location of Amphiphobic Antioxidants in Micellar Systems: The Diving-Swan Analogy - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C; Vidal-Palomo, M; Vidal-Palomo, M (Elsevier Ltd, 2019)
A protocol for determining the location of antioxidants (AOs) in a micro-heterogeneous medium was applied to three series of AOs with increasing hydrophobicities: chromancarboxylic acid (“Trolox”) esters, caffeic acid and its esters, and gallic acid and its esters. The observed paradoxical behaviour of these and other commonly encountered antioxidants was rationalized with the aid of a pictorial simile, the “diving-swan” analogy, that explains the orientation and location of an amphiphobic AO when it reacts with a radical probe in the micellar interface. © 2018 Elsevier Ltd